A review of factors that influence individual compliance with mass drug administration for elimination of lymphatic filariasis. - Alison Krentel; Peter U Fischer; Gary J Weil (Public Library of Science (PLoS), 2013)
Background The success of programs to eliminate lymphatic filariasis (LF) depends in large part on their ability to achieve and sustain high levels of compliance with mass drug administration (MDA). This paper reports results from a comprehensive review of factors that affect compliance with MDA. Methodology/principal findings Papers published between 2000 and 2012 were considered, and 79 publications were included in the final dataset for analysis after two rounds of selection. While results varied in different settings, some common features were associated with successful programs and with compliance by individuals. Training and motivation of drug distributors is critically important, because these people directly interact with target populations, and their actions can affect MDA compliance decisions by families and individuals. Other important programmatic issues include thorough preparation of personnel, supplies, and logistics for implementation and preparation of the population for MDA. Demographic factors (age, sex, income level, and area of residence) are often associated with compliance by individuals, but compliance decisions are also affected by perceptions of the potential benefits of participation versus the risk of adverse events. Trust and information can sometimes offset fear of the unknown. While no single formula can ensure success MDA in all settings, five key ingredients were identified: engender trust, tailor programs to local conditions, take actions to minimize the impact of adverse events, promote the broader benefits of the MDA program, and directly address the issue of systematic non-compliance, which harms communities by prolonging their exposure to LF. Conclusions/significance This review has identified factors that promote coverage and compliance with MDA for LF elimination across countries. This information may be helpful for explaining results that do not meet expectations and for developing remedies for ailing MDA programs. Our review has also identified gaps in understanding and suggested priority areas for further research.